A university-based model for space-related capacity building in emerging countries. (May 2016) - Polansky, John L.; Cho, Mengu
Abstract: Since 2011 the number of satellites less than 50 kg launched annually has increased by an order of magnitude. This trend is driven in part by proliferation of small satellite and lean satellite projects worldwide. In this decade alone, over 30 new countries are expected to achieve their first satellite in space. More than ever before, emerging countries are engaging in space-related activities. However, barriers such as lack of funding and underdeveloped human resources prevent many emerging nations from initiating or sustaining space programs. Kyushu Institute of Technology (Kyutech) has played an active role in space-related capacity building and international cooperation since 2009, then partnering with the United Nations Office for Outer Space Affairs to formulate a long-term fellowship programme hosted at Kyutech. Growing out of the success of the fellowship programme, Kyutech began significantly expanding its space-related capacity building project in 2013. This paper gives an overview of Kyutech's university-based model to enhance space-related capacity building and human resource development in emerging countries worldwide, and discusses advantages and disadvantages of alternative approaches.